PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU SMP NEGERI KOTA PALEMBANG - Detta Anastasya; Widiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the role of job satisfaction in mediating the influence of transformational leadership and school culture on teacher performance in public junior high schools (SMP Negeri) in Palembang City. Teacher performance faces challenges like limited teaching innovation and low professional development participation, influenced by inspirational leadership and collaborative culture. Data from 96 teachers used a validated 38-item questionnaire (r-calculated > r-table; Cronbach's Alpha > 0.90), analyzed via classical assumption tests and multiple regression. Results show transformational leadership (β=0.342, p=0.000) and school culture (β=0.259, p=0.000) significantly affect job satisfaction (R²=0.589), all influencing performance (R²=0.684, F=66.467, p=0.000), with job satisfaction mediating (Sobel Z=3.02; Z=3.05). Findings support Parsons' AGIL theory, recommending leadership training and inclusive culture enhancement. In conclusion, job satisfaction strengthens impacts on performance, urging educational management interventions.